Digital signal processing principles, devices and applications - Jones, N. B.; Watson, J. D. McK (P. Peregrinus on behalf of the Institution of Electrical Engineers, 1990)
The book reviews developments in the following fields: signal processing; discrete signals; Z-transforms; Fourier series; digital filters; FIR filter design; IIR filter design; state space control; Kalman filters; digital communication systems; DSP chips; microcontrollers; digital control; systolic arrays and speech processing.